Evaluating a Placemaking Approach for Public Space Regeneration - Pallavi Dalal; Vimala Swamy; Parag Narkhade (Calibrating Urban Livability in the Global South, 2024)
Placemaking is a concept and a strategy for increasing a location’s comfort, safety, and beauty so that people may enjoy their social lives. People are drawn to placemaking because it creates a feeling of place with varied emotional or aesthetic values. In contrast, the chaotic and uncontrolled growth of historic cities into modern metropolis makes the scenario unsustainable. By adopting the mechanism of placemaking we can explore the different place-making approaches to the cities, to restore and preserve the charter of place. This paper is an attempt understand the different approaches of placemaking with case studies that are equipped with better solutions. The investigation is sought to identify the obstacles to a desirable public area. To comprehend the significance of public places, a brief examination of their historical past was conducted. A study of the components and concepts that transform a common public space into a spectacular public space. Case studies on Western public spaces and Indian public spaces have been conducted to investigate the problematic and good aspects of public spaces, as well as the many variables that contribute to them.